Phytochemical analyses of Ziziphus jujuba Mill. var. spinosa seed by ultrahigh performance liquid chromatography-tandem mass spectrometry and gas chromatography-mass spectrometry - Yang, Bao (Royal Society of Chemistry, 2014)
Analyst